The Millennium Development Goals and Beyond - Feeny, Simon. author. aut Link
XI, 209 p.
Keywords: This book examines how international aid donors and Non-Governmental Organisations (NGOs) can assist countries in the Asia-Pacific region achieve the Millennium Development Goals. The book examines the progress countries have made towards the MDGs and highlights the need to tailor the goals to individual country circumstances.